TPACK Framework Towards 21st Century’s Pre-Service English Teachers: Opportunities and Challenges in Application - Nihta Vera Frelly Liando; Devilito Prasetyo Tatipang; Ceisy Nita Wuntu (Universitas Muhammadiyah Enrekang, 2023)
Learning in the 21st century integrates various technological devices in carrying out a whole series of interaction processes between students and teachers with learning resources in a learning environment. Pre-service English teachers in 21st century must have knowledge as well as skills in using various technologies, both traditional and modern to facilitate learning and improve learning outcomes. This article aims to examine, explain and review the development of technological pedagogical and content knowledge (TPACK) for Pre-service English teachers in 21st century, in order to obtain an overview of the opportunities and challenges in implementing TPACK itself in the 21st Century Learning. This article using a systematic review method of books, journal articles, and other documents related to the topic of discussion. All sources were selected based on the publication year that was set, namely 2017-2022 so that accurate and up-to-date data could be obtained. The results of the study found that, TPACK is a new type of knowledge that must be mastered by pre-service English teachers to be able to integrate technology well in learning. TPACK can be used as a framework for designing teacher education curricula that are more in line with the era and demands of 21st century learning